2011
DOI: 10.1111/j.1600-051x.2011.01798.x
|View full text |Cite
|
Sign up to set email alerts
|

MMP‐8 ‐799 C>T genetic polymorphism is associated with the susceptibility to chronic and aggressive periodontitis in Taiwanese

Abstract: These results suggested that non-smoking Taiwanese with the MMP-8 -799 T allele were associated with the risks of both CP and AgP. Further studies in other ethnic populations are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
(70 reference statements)
2
20
0
Order By: Relevance
“…1 , we initially identified 142 articles. Finally we included 16 articles 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 with 24 case-control studies involving 2,724 cases and 3,438 controls. Among them, there were four polymorphisms of MMP gene included in our meta-analysis: nine on MMP -9-1562 C/T, seven on MMP -3-1171 A5/A6, four on MMP -2-753C/T, and four on MMP -8-799 C/T.…”
Section: Resultsmentioning
confidence: 99%
“…1 , we initially identified 142 articles. Finally we included 16 articles 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 with 24 case-control studies involving 2,724 cases and 3,438 controls. Among them, there were four polymorphisms of MMP gene included in our meta-analysis: nine on MMP -9-1562 C/T, seven on MMP -3-1171 A5/A6, four on MMP -2-753C/T, and four on MMP -8-799 C/T.…”
Section: Resultsmentioning
confidence: 99%
“…, Chou et al. ) have rendered important clues to the pathogenesis of periodontal disease. However, most genetic association studies on periodontitis have usually included an individual population and a single or a few polymorphisms within a given gene, thus not capturing the complete genetic information of the region of interest (Schafer et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Chou et al. ). Nevertheless, most of these studies reflect investigation of an individual polymorphism in a single gene or in a couple of genes, which makes interpretation of the results difficult, taken the complexity of the MMP family and their compensatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the key roles of matrix metalloproteinase‐8 and tissue inhibitors of matrix metalloproteinase‐1 in periodontal tissues, it has been hypothesized that genetic variations influencing the transcription or function of these biomarkers contribute to susceptibility to generalized aggressive periodontitis. To date, only two studies have been reported of matrix metalloproteinase‐8 polymorphisms in relation to chronic periodontitis . On a genome‐wide level, no association of these polymorphisms has been found with either aggressive or chronic periodontitis.…”
Section: Possible Role Of Matrix Metalloproteinase‐8 Polymorphism In mentioning
confidence: 99%